(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Gamification has emerged as a transformative approach within Human Resource Management (HRM), enabling organizations to enhance employee motivation, engagement, and overall work experience. Although prior research has examined gamification across specific HR functions such as recruitment, training, and performance management, the literature remains fragmented, offering limited insight into its strategic role across the employee lifecycle. Addressing this gap, the present conceptual paper synthesizes interdisciplinary scholarship to develop an integrated lifecycle perspective of gamification in HRM. Drawing on Self-Determination Theory, Flow Theory, and Social Exchange Theory, the study explains how gamified practices activate psychological mechanisms that influence employee attitudes, behaviors, and organizational attachment from entry to long-term membership. The paper proposes a value-creation framework illustrating the progression from gamified HR practices to psychological activation, behavioral change, enhanced employee experience, and improved organizational outcomes. By positioning gamification as a strategic capability rather than a technological tool, this study contributes to theory development and advances understanding of experience-oriented HRM. The paper also outlines future research directions and offers managerial insights for designing ethically grounded and motivationally effective gamified work systems.